Yak milk fat globules from the Qinghai-Tibetan Plateau: Membrane lipid composition and morphological properties. (15th April 2018) - Luo, Jie; Huang, Ziyu; Liu, Hongna; Zhang, Yan; Ren, Fazheng
Highlights: Microstructures of yak and cow MFGM were compared. The presence of lipid domains in yak MFGM was reported for the first time. The heterogeneities were more significant in yak MFGM than cow MFGM. Yak milk has a higher cholesterol and sphingomyelin content compared to cow milk. Abstract: Yak milk fat products constitute the base of Qinghai-Tibetan pastoralists' daily food intake. Despite the great importance of fat in processing and pastoralists' health, studies about yak milk fat are scarce. In this study, the lipid composition and the morphological properties of milk fat globule membranes (MFGMs) of yak milk were investigated. The results demonstrated that the yak milk had a higher cholesterol and sphingomyelin content compared to cow milk. In situ structural investigations performed at 25 °C by confocal microscopy showed the presence of lipid domains in yak MFGM, with a larger number and wider size range compared to cow milk. Moreover, the simultaneous localization of glycosylated molecules and polar lipids indicated that glycosylated molecules could be integrated into the lipid domains in yak MFGM. Different characteristics in yak MFGM could be related to the lipid composition and may affect the functions of yak milk lipids during processing and digestion.